The Urgency of Village Owned Enterprise Contracts with Tourism Entrepreneurs - Yogahastama, Riesta; Shokhikhah, Zilda Khilmatus; Ramdhani, Mohammad Habib (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
In are two main approaches to tourism planning: the formal economic approach and the participatory approach, which emphasizes development and environmental conservation. In recent years, tourism management has increasingly shifted toward community- based models that highlight local participation and empowerment. Many Village-Owned Enterprises (BUMDes) are involved in tourism activities, forming business collaborations with entrepreneurs in areas such as homestays and souvenirs. However, problems often arise due to the absence of formal written agreements in these partnerships. Using a normative legal method, this research finds that agreements between BUMDes and tourism entrepreneurs should be in written form to uphold professionalism, accountability, and legal certainty. Written contracts also serve as valid evidence when disputes occur. Currently, regulations governing BUMDes do not specifically mandate written contracts for all business activities, leaving room for legal uncertainty. Since village communities often rely on oral agreements, revisions to government regulations are necessary to explicitly require written contracts in BUMDes’ civil relations with partners